An exploratory study on factors affected e-learning effectiveness in UUM - Chew, Jin Ying; Abu Al-Rejal, Hussein Mohammed Esmail (Universiti Utara Malaysia, 2020)
The objective of this study is to analyze the factors that affected the e-learning effectiveness. The method utilized in this study is quantitative which is providing the questionnaire to the students randomly. Six variables investigated in this study. Future researchers should increase the sample size by collecting data from different universities and colleges.